1978
DOI: 10.1136/hrt.40.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers and asthma.

Abstract: In a single-blind, randomised, crossover study in 10 asthmatic patients, the effects of approximately equipotent oral doses of 3 cardioselective beta-blockers-atenolol (100 mg), metoprolol (100 mg), and acebutolol (300 mg)-and 4 non-cardioselective beta-blockers-proranolol (100 mg), oxprenolol (100 mg), pindolol (5 mg), and timolol (10 mg) upon FEV1 were compared. All drugs, except pindolol, produced a significant reduction in standing pulse rate and prevented an increase in heart rate after inhaled isoprenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…However, because most receptors belong to large classes of evolutionaryrelated proteins that show high structural similarity, targeting a single receptor subtype is a major challenge. Poor selectivity can cause serious off-target side effects, as seen in the treatments of major depression (3), heart disease (4, 5), asthma (4,5), and allergies (6).…”
mentioning
confidence: 99%
“…However, because most receptors belong to large classes of evolutionaryrelated proteins that show high structural similarity, targeting a single receptor subtype is a major challenge. Poor selectivity can cause serious off-target side effects, as seen in the treatments of major depression (3), heart disease (4, 5), asthma (4,5), and allergies (6).…”
mentioning
confidence: 99%
“…Although P-adrenoceptor blockade is not the treatment of choice in these situations, atenolol, a cardioselective 3-adrenoceptor blocker may be used as daily doses below 100 mg have little effect on airway resistance (Decalmer et al, 1978;Ellis et al, 1981;Lawrence et al, 1983 On each study day, theophylline was administered intravenously as aminophylline (ElkinsSinn, Inc., Cherry Hill, New Jersey; Lot #: 066074 containing 79.36% theophylline). Approximately a 6 mg kg-' (ideal body weight) dose was infused over 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…The bronchial response to an inhaledadrenoceptor agonist, usually isoprenaline or salbutamol, has been used in many clinical studies. Decalmer et al (1978), Thiringer & Svedmyr (1976), Ryo & Townley (1976) Mattson & Poppius (1978), Beumer et al (1978 and Benson etal. (1977), have all shown that the non-selective 1-adrenoceptor antagonists, with or without partial agonist properties, tend to prevent the inhaled bronchodilator airway response more than the PI1 selective antagonists, and more than placebo.…”
Section: Resultsmentioning
confidence: 99%